1990
DOI: 10.1017/s0016672300035229
|View full text |Cite
|
Sign up to set email alerts
|

Conserved loci on the X chromosome confer phosphate homeostasis in mice and humans

Abstract: Several genes expressed in kidney and other tissues determine phosphate homeostasis in extracellular fluid. The major form of inherited hypophosphatemia in humans involves an X-linked locus (HPDR, Xp22.31-p21.3). It has two murine homologues (Hyp and Gy) which map to closely-linked but separate loci (crossover value 0.4%-0.8%). Both murine mutations impair Na(+)-phosphate cotransport in renal brush border membrane; an associated renal disorder of 1,25-dihydroxyvitamin D3 (1,25(OH)2D) metabolism has been charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 93 publications
(88 reference statements)
2
8
0
Order By: Relevance
“…Mutations in homologous genes on the human (HYP) and mouse (Hyp) X chromosomes are responsible for X-linked hypophosphatemia, a disorder in renal Pi reabsorption characterized by rachitic bone disease ( 1,5). In the present study, we demonstrate that the specific defect in Na '-dependent Pi transport in the renal brush border membrane of Hyp mice (6,7,10) is associated with a specific decrease in the renal abundance of Na+-Pi cotransporter mRNA and protein.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Mutations in homologous genes on the human (HYP) and mouse (Hyp) X chromosomes are responsible for X-linked hypophosphatemia, a disorder in renal Pi reabsorption characterized by rachitic bone disease ( 1,5). In the present study, we demonstrate that the specific defect in Na '-dependent Pi transport in the renal brush border membrane of Hyp mice (6,7,10) is associated with a specific decrease in the renal abundance of Na+-Pi cotransporter mRNA and protein.…”
Section: Discussionsupporting
confidence: 48%
“…Like their human counterparts, Hyp mice are characterized by rachitic bone disease, hypophosphatemia, and impaired renal reabsorption of filtered phosphate (Pi)' (1,2). In both mouse (3) and humans (4), the mutation maps to one offive highly conserved regions on the X chromosome (5). Neither the gene nor its product have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is important to consider the results of studies in humans and mice with X-linked hypophosphatemia, a dominant disorder of P i homeostasis associated with impaired skeletal mineralization and caused by inactivating mutations in the PHEX/Phex gene (37). The disease phenotype is as severe in affected males and females (31,43), as well as in female mice carrying either one or two copies of the mutant allele (31, 32, 35). These findings, which provide evidence for haploinsufficiency of PHEX (41), indicate that PHEX protein produced from the wild-type allele in affected heterozygous females does not reach the threshold level necessary for normal function and that the disease phenotype is manifest in the face of a 50% decrease in PHEX expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is a dominant disorder of phosphate homeostasis characterized by rachitic and osteomalacic bone disease, short stature, hypophosphatemia, and renal defects in phosphate reabsorption and vitamin D metabolism (2). Much of our knowledge of the human disease is derived from studies of the murine Hyp mutation (2)(3)(4)(5), which maps to a region of the mouse X chromosome that is syntenic to the XLH ( HYP ) locus on the human X chromosome (6). We demonstrated that Hyp mice have a specific defect in phosphate transport across the renal brush border membrane that is associated with a decrease in high affinity Na ϩ -phosphate cotransport V max (7) and can be ascribed to a decrease in renal abundance of type II Na ϩ -phosphate cotransporter ( Npt2 ) mRNA and immunoreactive protein (8).…”
Section: Introductionmentioning
confidence: 99%